STUDI KUALITATIF PENGELOLAAN SAMPAH DI KECAMATAN BANYUMANIK KOTA SEMARANG - Dipika Fatma Nudiana; Tri Yuniningsih; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2015)
Increasing population growth in Sub Banyumanik effect by increasing the amount of waste from year to year. Waste management system is needed to address the problems that arise as a result of waste overload. The aim of this study was to determine the condition of waste management, as well motivating factor inhibiting factor and waste management solutions in the District Banyumanik. The research method used is descriptive qualitative research methods. The results showed that the waste management in the city of Semarang, especially in Sub Banyumanik yet either. There are still obstacles that make waste management, especially at the stage of transporting waste from TPS to landfill and waste processing stage less running smoothly. Automaticaly the service quality provided to the public by the waste management officer can not be maximized. The writer suggests that the addition of waste management facilities and infrastructure in the form of TPS, the government together with the Institute of Public Social socializes The Waste Management System (3R) to the public periodically. The Department of Hygiene and Urban Landscapping of Semarang together with coordinator / Sub District Hygine officer of Banyumanik need to evaluate hygiene care facilities needs by adapted to the number and distribution of the population.